The process for adopting Robotic Process Automation in the South African Banking Sector - Mongwe, Mamelo Christina (University of the Witwatersrand, Johannesburg, 2024)
The banking industry in South Africa has taken a major step towards digital transformation with the use of Robotic Process Automation (RPA). The goals of this change are to increase operational efficiencies, boost customer service, and preserve competitive advantage in a financial landscape that is changing quickly. This calculated action marks a turning point in the adoption of cutting-edge technologies by South African banks, enabling them to better manage the intricacies of regulatory compliance, cut expenses, and streamline operations. This study explores the use of RPA in South Africa's banking industry, concentrating on the drivers, challenges, and impact of RPA integration in this setting. As the South African banking sector leads the way in adopting digital innovations to improve customer service and operational savings, RPA stands out as a key tool for optimising workflows and cutting expenses. This research adopted a qualitative research method, including semi-structured interviews for data collection, using a purposive sampling technique for participants selection and data analysed using thematic analyses. A total of 10 participants who contribute towards the adoption and implementation of RPA within various banks within South Africa were interviewed. The findings show that organisational culture, legal frameworks, and technology readiness interact intricately to shape RPA initiatives. The study also emphasises how important governance structures and stakeholder participation are in overcoming adoption-related obstacles to RPA. This study broadens the understanding of RPA's role in the financial sector's digital transformation by providing insights into the experiences of South African banks. It also offers recommendations for future research in the subject and consequences for practitioners
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Robotic Process Automation; Digital Transformation in Banking; Financial Services Innovation; Operational Efficiency in Banking; Technological Innovation in Banking; SDG-8: Decent work and economic growth